Tourist cycling trips in the tropics; The ideological landscape of recreational bike rides in the former Netherlands East Indies at the end of the nineteenth century - Tomberge, Nick (UI Scholars Hub, 2024)
Although previous research shows that the introduction of bicycles drove recreational travel in Western Europe, North America, and Australia, to this day, little is known about tourist cycling in other parts of the world. Nevertheless, a broader geographical context is desirable: the study of the early days of tourist cycling in former European colonies in Southeast Asia can enhance our understanding of the strong political dimensions of tourist travel in a colonial context, as it is interconnected with the project of imperialism, technological change, and modernity. This article examines the early days of tourist cycling in the former Netherlands East Indies from 1884 to 1900. The central questions are: What were the communicated experiences of cycling tourists in the Netherlands East Indies in the late nineteenth century? And what were the ideological foundations underlying their experiences? The research corpus consists of the issues of De Kampioen – the magazine of the Dutch bicycle association ANWB – from this period. It indicates that tourist cycling emerged in various forms in the Netherlands East Indies at the end of the nineteenth century. Whereas most of the Dutch cyclists’ texts that have been examined, strongly emphasize an aesthetic experience, the Australians Burston and Stokes, as the epitome of imperial self-assurance, describe their journey in their travel text more emphatically as dangerous and thereby as a form of adventure tourism. Although the ANWB had some Asian and female members before 1900, episodes of De Kampioen from the nineteenth century extol the physical achievements of Western men. In doing so, these androcentric accounts also underscore the European patriarchal system and the racial hierarchy that supported Dutch colonialism in Southeast Asia.